Business cycle synchronization and insurance mechanisms in the EU - Afonso, António (2010)
In this paper we provide a positive exercise on past business-cycle correlations and risk sharing in the European Union, and on the ability of insurance mechanisms and fiscal policies to smooth income fluctuations. The results suggest in particular that while some of the new Member States have well synchronized business cycles, for some of the other countries, business cycles are not yet well synchronized with the euro area's business cycle, and risk-sharing mechanisms may not provide enough insurance against shocks.